CD4+ and CD8+ CD28null T Cells Are Cytotoxic to Autologous Muscle Cells in Patients With Polymyositis. Issue 8 (27th July 2016) - Pandya, Jayesh M.; Venalis, Paulius; Al‐Khalili, Lubna; Shahadat Hossain, Mohammad; Stache, Vanessa; Lundberg, Ingrid E.; Malmström, Vivianne; Fasth, Andreas E. R.
Abstract : Objective: Inflammatory T cell infiltrates in the skeletal muscle tissue of patients with polymyositis are dominated by CD28‐negative effector (CD28 null ) T cells of both the CD4 and CD8 lineage. These cells are potentially cytotoxic, and the aim of the present study was to develop a fully autologous cell culture system in which to investigate the functional contribution of such CD28 null T cells to myotoxicity. Methods: In vitro cocultures of autologous skeletal muscle cells and T cell subsets obtained from 5 polymyositis patients were performed. Myotoxicity of T cells was quantified by calcein release and flow cytometric analyses. T cell degranulation was blocked with concanamycin A. Specific blocking of perforin, cytokines, and HLA was performed using antibodies. Results: Both CD4+CD28 null and CD8+CD28 null T cells induced more muscle cell death than did their CD28+ counterparts. Differentiated muscle cells (myotubes) were more sensitive to T cell–mediated cell death than were their precursors (myoblasts). Both CD8+ and CD4+ CD28 null T cells displayed perforin polarization toward muscle cells and secreted higher levels of granzyme B and interferon‐γ (IFNγ) in coculture than did CD28+ T cells. The myotoxic effects of CD28 null T cells were reduced upon the blocking of perforin, cytokines, and HLA. Addition of IFNγ or tumor necrosis factor did not induce skeletal muscle cell death in the absence of T cells; however, it did up‐regulate HLA expression on muscle cells. Conclusion: Myotoxicity of CD4+ and CD8+ CD28 null T cells is mediated by directed perforin‐dependent killing and can be further influenced by IFNγ‐induced HLA expression on muscle cells. The data suggest that CD28 null T cells are key effector cells that contribute to the muscle cell damage in polymyositis.